In vitro isolation and identification of entomopathogenic fungus (Metarhizium pinghaense) and assessment of its virulence against whiteflies and aphids - Haiyan Hu; Yali Wang; Chunyan Li; Ranran Zhang; Fangyu Liu; Xiaoan Sun (PLoS ONE, 2026)
Bemisia tabaci (Gennadius) and Aphis gossypii (Glover) are two notorious pests of vegetables grown in greenhouses and their outbreaks can be devastating and cause a significant loss in yield and quality. The prevail and effective control of the pests mainly relies on frequent applications of pesticides, which is likely to negatively impact environments and human health through residue, resurgence, and resistance. To avoid negative “3R” issues brought forth by chemicals, entomopathogenic fungus such as Metarhizium sp. are widely used as biocontrol agents even if they are different in their population, adaptability and pathogenicity among various species and isolates collected from different insect hosts and environments. To screen for the entomopathogenic fungi with optimal pathogenicity against the piercing-sucking pests B. tabaci and A. gossypii , we have isolated, purified four strains (SG-A, SG-B, SG-C, and SG-D) of Metarhizium sp. using yellow mealworms ( Tenebrio molitor ) as the bait, and identified them as Metarhizium pinghaense morphologically and molecularly. Bioassay results have indicated that four isolates of M. pingshaense infected both B. tabaci and A. gossypii with some differences in the virulence and median lethal time. Both B. tabaci and A. gossypii nymphs showed an increase in the mortality rate as the spore concentration rose. Four M. pingshaense strains also exhibited the different pathogenicity against B. tabaci and A. gossypii at various levels: At an inoculum concentration of 1 × 10 8 conidia/mL, the cumulative corrected mortality of B. tabaci nymphs 8 days post-treatment ranked in the order: SG‑A > SG‑C > SG‑B = SG‑D. For A. gossypii , the cumulative corrected mortality followed the order: SG‑A > SG‑B > SG‑D > SG‑C.Strain SG-A demonstrated the maximized pathogenicity against nymphs of B. tabaci and A. gossypii 8 days after the treatment (LC 50 = 7.00 × 10 4 and 4.21 × 10 5 conidia/mL, respectively). At the spore concentration at 1 × 10 8 conidia/mL, its cumulatively corrected mortality reached 94.44% and 96.67% (LT 50 = 4.13 d and 2.61 d, respectively). Strain SG-C showed an optimal pathogenicity against B. tabaci nymphs only with a cumulative corrected mortality of 87.78% and an LT 50 at 4.30 d 8 days after the treatment. In contrast, strain SG-B exhibited relatively high pathogenicity against A. gossypii nymphs only with a cumulative corrected mortality of 72.22% and an LT 50 at 2.31 d 8 days after the treatment. Therefore, M. pinghaense SG-A should be a potential biocontrol agent to manage whiteflies and aphids at their nymph stage during the vegetable production season.